ANALYSIS OF FACTORS ASSOCIATED WITH UNMET NEED FOR FAMILY PLANNING AMONG WOMEN OF REPRODUCTIVE AGE - Sharfina Haslin; Dewi Risma Uli Br Bancin; Elisa Aritonang; Juneris Aritonang (Jurnal Biometrika dan Kependudukan, 2026)
Unmet need for contraception is a significant demographic phenomenon that affects the success of family planning programs. A high prevalence of unmet need contributes to unintended pregnancies, which can adversely affect maternal and child health. This study aimed to analyze the factors associated with unmet need for family planning among women of reproductive age in Mekar Sari Village, Deli Serdang Regency. A quantitative cross-sectional design was employed. The study population consisted of 155 married women of reproductive age, from whom 61 respondents were selected using accidental sampling . Bivariate analysis using the chi-square test revealed significant associations between unmet need and family income (p=0.001), husband’s support (p=0.004), and women's knowledge (p=0.002). Among these variables, family income showed the strongest association with unmet need. These findings suggest that addressing economic, spousal support, and educational factors is essential for reducing unmet need among women of reproductive age. Efforts to reduce unmet need should therefore include strengthening family economic well-being, improving women's knowledge of contraception, and enhancing husband involvement in family planning programs.